Gene Deletions and Prognostic Values in B-Linage Acute Lymphoblastic Leukemia - Fang, Qiuyun; Song, Yang; Gong, Xiaoyuan; Wang, Jun; Li, Qinghua; Liu, Kaiqi; Feng, Yahui; Hao, Qishan; Li, Yan; Wei, Hui; Zhang, Guangji; Liu, Yuntao; et al. (Frontiers in Oncology, 2021)
Although pediatric-like treatment regimen has remarkably improved the survival rates of adults with acute lymphoblastic leukemia (ALL), the outcome of some adult patients is still poor owing to adverse genetic features. These molecular abnormalities, especially gene deletions, may be considered for the prognosis assessment for adult patients with ALL. In this study, using multiplex ligation dependent probe amplification (MLPA) method, gene deletions were analyzed in from 211 adult B-ALL patients treated in our center. The data showed that 68.2% (144/211) adult B-ALL patients carried gene deletions, and the frequency is much higher in Ph+B-ALL patients. IKZF1 gene deletion is the most common gene deletion in adult B-ALL, followed by CDKN2A/B deletion. In Ph-B-ALL patients, the overall survival of patients with gene deletions is inferior to that of patients without any gene deletions. More obviously, patients with IKZF1 or CDKN2A/B deletion had a worse prognosis, whereas, allogeneic hematopoietic stem cell transplantation could improve OS in patients with IKZF1 deletion, but not in patients with CDKN2A/B deletion. Moreover, the outcome of Ph-B-ALL patients with double deletion of IKZF1and CDKN2A/B may be much worse than that of patients with IKZF1 or CDKN2A/B alone. Minimal residual disease (MRD) was also analyzed together with gene deletions and demonstrated that gene deletions have a negative impact on survival only in MRD positive Ph-B-ALL patients. In conclusion, gene deletions are closely related with the prognosis of adult Ph-B-ALL patients.